Relationship between circulating n-3 fatty acid concentrations and endothelial function in early adulthood. - Leeson, C; Mann, A; Kattenhorn, M; Deanfield, J; Lucas, A; Muller, D (2002)
AIMS: Fish consumption is inversely associated with cardiovascular mortality, presumably because of n-3 fatty acids in fish. Whether the protection of n-3 fatty acids extends beyond clinical coronary disease to influence the early vascular biology of atherosclerosis remains unclear. This study determined whether circulating levels of n-3 fatty acids are associated with vascular endothelial function in early adulthood. METHODS AND RESULTS: Three hundred and twenty-six adults (157 males, 169 females, aged 20 to 28 years) had high-resolution ultrasound measurements of flow-mediated brachial artery dilatation (FMD) (endothelium-dependent) and arterial response to glyceryl trinitrate (endothelium-independent). Levels of the n-3 fatty acids docosahexaenoic acid (DHA) and eicosapentaenoic acid in plasma and erythrocyte membranes of subjects were measured. n-3 Fatty acid levels were not related to vascular function in the whole group. In smokers, however, n-3 fatty acids were positively related to flow-mediated dilatation (plasma DHA vs. FMD: 0.045 mm. %(-1), 95% CI 0.011 to 0.079, P=0.01). Flow-mediated dilatation was also associated with n-3 fatty acid levels in subjects in the top third of the insulin, glucose and triglyceride distributions. CONCLUSION: In young smokers and those with higher fasting insulin, glucose or triglyceride concentrations (factors associated with endothelial dysfunction), n-3 fatty acid levels were positively associated with flow-mediated dilatation. This raises the possibility that physiological levels of circulating n-3 fatty acids may protect the endothelium from early adulthood.